2013
DOI: 10.1002/emmm.201202218
|View full text |Cite
|
Sign up to set email alerts
|

SRSF1 and SRSF9 RNA binding proteins promote Wnt signalling‐mediated tumorigenesis by enhancing β‐catenin biosynthesis

Abstract: Wnt/β-catenin signalling is widely implicated in embryogenesis, tissue homeostasis and tumorigenesis. The key event in Wnt signalling activation is β-catenin accumulation, which is controlled by both its production and degradation. However, much more emphasis has been placed on the understanding of its degradation. Here, we show that the synthesis of β-catenin protein, which requires a group of serine/arginine-rich splicing factors (SRSF), also contributes to its tumorigenic activity. Overexpression of SRSF1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
105
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(117 citation statements)
references
References 80 publications
8
105
0
1
Order By: Relevance
“…Although the mechanisms of β-catenin protein degradation are well-described, comparatively little is known about the regulation of its production 24 . Consistent with our findings, others have shown that RBPs can modulate CTNNB1 mRNA metabolism and β-catenin protein expression 25 - 29 . Although a previously published study did not identify a decrease in β-catenin protein expression in hnRNPA2-depleted cells, 7 this may be due to functional redundancy as exemplified by complex mRNA transcript cross- and auto-regulation by hnRNP paralogs 14 , 30 .…”
Section: Discussionsupporting
confidence: 87%
“…Although the mechanisms of β-catenin protein degradation are well-described, comparatively little is known about the regulation of its production 24 . Consistent with our findings, others have shown that RBPs can modulate CTNNB1 mRNA metabolism and β-catenin protein expression 25 - 29 . Although a previously published study did not identify a decrease in β-catenin protein expression in hnRNPA2-depleted cells, 7 this may be due to functional redundancy as exemplified by complex mRNA transcript cross- and auto-regulation by hnRNP paralogs 14 , 30 .…”
Section: Discussionsupporting
confidence: 87%
“…The synthesis of ␤-catenin is controlled by two splicing factors, SRSF1 and 9, exhibiting an aging-related decrease [296] that could explain the Wnt/␤-catenin signaling defect. The same two SRSF are overexpressed in cancer cells and promote Wnt-signaling tumorigenesis through the production of ␤-catenin mRNA [367].…”
Section: Adult Stem Cell Exhaustion Related To Defects In Signaling Pmentioning
confidence: 99%
“…Moreover, SRSF1, -3, and -9 are overexpressed in a number of cancers and possess oncogenic properties (22,26,31). Previously, we reported increased levels of the three smallest SR proteins, SRSFs 1 to 3, in our W12 model of cervical tumor progression and in patient samples (24).…”
Section: Discussionmentioning
confidence: 61%
“…Unsurprisingly, due to their diverse functions, many SR proteins are overexpressed in a range of tumors (21)(22)(23)(24)(25). Importantly, SRSF1 (ASF/SF2), SRSF3 (SRp20), and SRSF9 (SRp30c) have been shown to possess oncogenic properties (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Increased SRSF levels can result in the production of alternatively spliced RNA isoforms encoding key antiapoptotic, cell proliferation, and epithelial-mesenchymal transition (EMT)-inducing proteins (18).…”
mentioning
confidence: 99%